Phytochemical Profiles and Antimicrobial Activity of Selected Populus spp. Bud Extracts - Piotr Okińczyc; Jarosław Widelski; Kinga Nowak; Sylwia Radwan; Maciej Włodarczyk; Piotr Marek Kuś; Katarzyna Susniak; Izabela Korona-Głowniak (Molecules, 2024)
Buds of poplar trees (Populus species) are often covered with sticky, usually polyphenol-rich, exudates. Moreover, accessible data showed that some Populus bud extracts may be excellent antibacterial agents, especially against Gram-positive bacteria. Due to the fragmentary nature of the data found, we conducted a systematic screening study. The antimicrobial activity of two extract types (semi-polar—ethanolic and polar—ethanolic-water (50/50; V/V)) from 27 bud samples of different poplar taxons were compared. Antimicrobial assays were performed against Gram-positive (five strains) and Gram-negative (six strains) bacteria as well as fungi (three strains) and covered the determination of minimal inhibitory, bactericidal, and fungicidal concentrations. The composition of extracts was later investigated by ultra-high-performance liquid chromatography coupled with ultraviolet detection (UHPLC-DAD) and with electrospray-quadrupole-time-of-flight tandem mass spectrometry (UHPLC-ESI-qTOF-MS). As a result, most of the extracts exhibited good (MIC ≤ 62.5 µg/mL) or moderate (62.5 < MIC ≤ 500 µg/mL) activity against Gram-positives and Helicobacter pylori, as well as fungi. The most active were ethanolic extracts from P. trichocarpa, P. trichocarpa clone ‘Robusta’, and P. tacamahaca × P. trichocarpa. The strongest activity was observed for P. tacamahaca × P. trichocarpa. Antibacterial activity was supposedly connected with the abundant presence of flavonoids (pinobanksin, pinobanksin 3-acetate, chrysin, pinocembrin, galangin, isosakuranetin dihydrochalcone, pinocembrin dihydrochalcone, and 2′,6′-dihydroxy-4′-methoxydihydrochalcone), hydroxycinnamic acids monoesters (p-methoxycinnamic acid cinnamyl ester, caffeic acid phenethylate and different isomers of prenyl esters), and some minor components (balsacones).